Collaborative Governance in Enforcement Program for Restrictions on Community Activities in Bandung City - Andre Ariesmansyah; Dea Melati (Program Pascasarjana Universitas Negeri Makassar, 2021)
The increase in community mobility after Eid al-Fitr has had a significant influence on the surge in Covid-19 cases in Indonesia. The city of Bandung is one of the cities with a high level of community activity, thus making the increase in positive cases of COVID-19 difficult to control. In accordance with the emergency policy set by the central government for the implementation of restrictions on the activities of the Java-Bali community, the Bandung City government made PPKM a progressive strategy implemented to reduce the critical number of COVID-19 by involving various stakeholders to accelerate efforts to deal with COVID-19. This study uses qualitative methods with descriptive analysis techniques to examine holistically the object of the research problem in accordance with the theories and concepts used as a knife of analysis in research. Thus the data presented is expected to be able to provide an overview that can be understood systematically and methodically in accordance with the data and facts in the field. In this study, it can be concluded that the success of the PPKM program in the city of Bandung is not able to stand alone, but there needs to be a harmonious synergy that is built on all elements of implementing the PPKM program. Through cross-sectoral collaboration that is integrated in the concept of collaborative governance, the goal of implementing PPKM in Bandung City can be realized by minimizing distortions that may occur as a result of overlapping policies.